A Concept of the Effective Surface Profile to Predict the Roughness Parameters of Worn Surface - Kovalev, Alexander; Yazhao, Zhang; Hui, Cao; Meng, Yonggang (Frontiers in Mechanical Engineering, 2019)
A new concept of the effective surface profile is proposed to facilitate the prediction of the worn surface texture at sliding friction. The effective surface profile is a 2D height characteristic that consists of the asperities of surface superimposed on a plane perpendicular both to the mean surface plane and to the direction of sliding. We hope to present a clear and compelling argument favoring the use of the effective surface profile as a versatile tool for characterization of rough surfaces at abrasive wear, calculation of contact characteristic at sliding friction, and for prediction of evolution of roughness parameters from virgin to the worn surfaces. The effective surface profile can be successfully applied for investigations of sliding abrasive wear under dry or lubricated conditions.